Madam President - Lane Smith (New York, NY, United States Hyperion Books for Children, 2008)
d
Keywords: Circle Time Books - Stereotypes / Identity / Diversity/ Gender Roles -- Circle Time Books - Stereotypes / Identity / Diversity/ Gender Roles